Correct Answer - Option 2 : 3

**Given:**

Given equation = 5x^{2} – 9x + 3

**Concept:**

Sum of roots = – (coefficient of x)/(coefficient of x^{2})

Product of roots = (constant)/(coefficient of x^{2})

**Calculation:**

Sum of the roots,

a + b = –(–9)/5 = 9/5

Product of the roots, ab = 3/5

According to the problem,

⇒ (1/a) + (1/b)

⇒ (b + a)/ab

⇒ (9/5)/(3/5)

⇒ 3

**∴ value of (1/a) + (1/b) is 3.**

** **Sum of roots = -b/ a

Product of roots = c/ a

Subtraction of roots = √D/ a

where equation is ax2 + bx + c and D = √ (b2 - 4ac)